2017
DOI: 10.18632/oncotarget.16989
|View full text |Cite
|
Sign up to set email alerts
|

Impact of marital status during diagnosis on cancer-caused specific survival in acute myeloid leukemia patients: a case-control and population-based study

Abstract: ObjectiveThis study investigated the impact of marital status on cancer-caused specific mortality among acute myeloid leukemia (AML) patients in the United States.MethodsWe used the Surveillance, Epidemiology and End Results program to identify 50,825 patients who had their clinical and follow-up information available and were diagnosed for AML between the years 1988 and 2015. The univariate and multivariable Cox regression models were used to analyze the patient data, and to minimize the group differences due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Consistent with the data of solid tumors, marital status is closely associated to the risk of AML-related death. Compared with unmarried AML patients, married or cohabitating counterparts had a lower risk of death [27,39]. In terms of socioeconomic status, the prognosis of AML's patients with low-income or residing in poverty-stricken regions was relatively poorer [3,40].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the data of solid tumors, marital status is closely associated to the risk of AML-related death. Compared with unmarried AML patients, married or cohabitating counterparts had a lower risk of death [27,39]. In terms of socioeconomic status, the prognosis of AML's patients with low-income or residing in poverty-stricken regions was relatively poorer [3,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, the independent prognostic value of these factors has not been consistent across studies. [24][25][26][27][28][29] Our study also examines the association between these factors and disease/symptom burden and survival in patients with MM. While most studies use neighborhood characteristics to estimate SES, this study utilizes the HOUSES index, a measure derived from individual housing characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Marital status has been reported to be associated with survival in patients with several types of cancer, including acute myeloid leukemia, and those receiving solid organ transplantation [1][2][3][4][5]. However, there have been no reports detailing the impact of marital status on outcomes after allogeneic hematopoietic cell transplantation (HCT).…”
mentioning
confidence: 99%
“…Several studies have shown that marital status affected cancer-specific mortality among patients with solid cancer and acute myeloid leukemia [1][2][3][4], whereas other studies have not [9]. The reason for the correlation of marital status and improved cancer-specific survival has been unclear, but one possible reason is that married patients have better adherence to prescribed treatments than unmarried patients [10].…”
mentioning
confidence: 99%